CRISPR/Cas9 based blockade of IL-10 signaling impairs lipid and tissue homeostasis to accelerate atherosclerosis - Shi, Haozhe; Guo, Jiabao; Yu, Qiongyang; Hou, Xinlin; Liu, Lili; Gao, Mingming; Wei, Lili; Zhang, Ling; Huang, Wei; Wang, Yuhui; Liu, George; Tontonoz, Peter; et al. (Frontiers in Immunology, 2022)
Interleukin-10 (IL-10) is a widely recognized immunosuppressive factor. Although the concept that IL-10 executes an anti-inflammatory role is accepted, the relationship between IL-10 and atherosclerosis is still unclear, thus limiting the application of IL-10-based therapies for this disease. Emerging evidence suggests that IL-10 also plays a key role in energy metabolism and regulation of gut microbiota; however, whether IL-10 can affect atherosclerotic lesion development by integrating lipid and tissue homeostasis has not been investigated. In the present study, we developed a human-like hamster model deficient in IL-10 using CRISPR/Cas9 technology. Our results showed that loss of IL-10 changed the gut microbiota in hamsters on chow diet, leading to an increase in lipopolysaccharide (LPS) production and elevated concentration of LPS in plasma. These changes were associated with systemic inflammation, lipodystrophy, and dyslipidemia. Upon high cholesterol/high fat diet feeding, IL-10-deficient hamsters exhibited abnormal distribution of triglyceride and cholesterol in lipoprotein particles, impaired lipid transport in macrophages and aggravated atherosclerosis. These findings show that silencing IL-10 signaling in hamsters promotes atherosclerosis by affecting lipid and tissue homeostasis through a gut microbiota/adipose tissue/liver axis.